Penguatan Media Promosi Andi Rattan Furniture melalui Fotografi - Iman, Priaji; Raina, Pratita Rara; Ridlo, M. Harun Rosyid (Abdi Seni, 2025)
Community service or PKM aims to create a catalogue of Andi Rattan Furniture products as promotion media through product photography. Trangsan Village, as one of the rattan industry centers in Sukoharjo, faces challenges in expanding its market reach, especially for small to medium craftsmen who rely on third parties for access to product export, including Andi Rattan Furniture. The main problems faced were the lack of marketing staff and the minimal use of digital media for product promotion. The participatory action research (PAR) approach is used in this activity to empower partners with solutions in aspects of business management and digital marketing, including product photography training and e-commerce usage. The results of the activity show that through improving business management, creating product catalogs, and activating social media, Andi Rattan Furniture can expand its market reach and increase product competitiveness at local and international levels. Continuous assistance and the implementation of digital marketing strategies are expected to support Andi Rattan Furniture sustainable businesses. Keywords: Creative Economy, Rattan, PAR, Community Service